A study on relationship between customer satisfaction, service quality and customer loyalty at Telekom Malaysia Berhad - Md Ibrahim, Nurmalis (2006)
This research is about a study on relationship between customer satisfaction, service quality and customer loyalty at Telekom Malaysia Berhad, Kota Bharu, Kelantan. Factors such as service quality and customer loyalty have been identified in order to investigate whether or not these factors have a relationship with customer satisfaction. The survey is conducted at Telekom Malaysia Berhad Kota Bharu, Kelantan. The sample size for this study is 100 customers from Telekom Malaysia Berhad. There were 120 questionnaires were distributed but only 100 were returned. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain element that potentially have relationship with customer satisfaction, service quality and customer loyalty. Data are analyzed using Reliability Test, Pearson Correlation Analysis, Multiple regression analysis, Descriptive statistics as well as Gap analysis through SPSS Program. The result shows that in service quality, tangible and reliability are two dimensions that most influence customer satisfaction towards Telekom Malaysia. The other three dimensions which are responsiveness, empathy and assurance do not have significant relationship on customer satisfaction. Customer loyalty was found to have significant relationship with customer satisfaction.